IMPLEMENTASI LESSON STUDY BERBASIS DISCOVERY LEARNING TERHADAP HASIL BELAJAR FISIKA DI MADRASAH ALIYAH NEGERI 2 PAMEKASAN - Muhammad Hasbullah; Fathiyatur Rohmah; Fitriyatus Sholehah; Sri Agustiningsih (Journal of Education Partner, 2023)
This research aims to determine the implementation of discovery learning-based lesson study on student learning outcomes in capacitor material in class XII IPA 4 MAN 2 Pamekasan. In this research, the research method used in this research uses a descriptive qualitative approach with a phenomenological type, the data collection methods used are interviews, field observations and documentation data analysis, while the research location is at Madrasah Aliah Negeri 2 Pamekasan, class XII, Science Department. The subjects in this research were students of class XII Science 4 MAN 2 Pamekasan with a total of 28 students. The results of the research show that the implementation of lesson study based on discovery learning needs to carry out three stages, namely 1) plan (planning), namely a model teacher with an observer preparing learning needs in the class, starting from determining material, preparing lesson plans, using media, models, methods and strategies in teaching, and the concept of the learning process in the classroom must be mutually agreed upon. 2) Do (Implementation and Observation), namely carrying out the results of planning and expressing them in the classroom learning process. Observers are tasked with seeing/observing things they find interesting or students they find interesting. The final stage is 3) See (Reflection) at this stage the teacher (model) and observer discuss together what weaknesses existed during the implementation of the lesson.